APOSTILLAS A ALGUNAS LECTURAS DISCREPANTES EN LAS EDICIONES DE LIBRO DE ALEXANDRE - Pejenaute Rubio, Francisco (Myrtia, 2008)
The different editions of the ’Libro de Alexandre’, both scientific and popular, frequently offer readings -especially those concerning proper names- not just different but even extraordinarily divergent. In such instances it would have been most convenient to compare those passages with the corresponding ones in Gautier de Châtillon’s ’Alexandreis’, as this is the primary source of the ’Libro’..., but inasmuch as the collation would be effected with a critical edition such as that published by M.L. Colker (1978). Colker’s edition, although worth improving, has superseded the older editions by F.A.W. Müldener (1863) and that printed in the ’Patrologia Latina’ (as it is just a reproduction of that by A. Gugger, 1659), that, nevertheless, are still used by some editors of the Libro de Alexandre.